2014
DOI: 10.1021/pr500467d
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Proteome Profile Predictive of Disease Activity in Rheumatoid Arthritis

Abstract: Current serum biomarkers for rheumatoid arthritis (RA) are not highly sensitive or specific to changes of disease activities. Thus, other complementary biomarkers have been needed to improve assessment of RA activities. In many diseases, urine has been studied as a window to provide complementary information to serum measures. Here, we conducted quantitative urinary proteome profiling using liquid chromatography-tandem mass spectrometry (LC-MS/MS) and identified 134 differentially expressed proteins (DEPs) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 54 publications
(86 reference statements)
3
27
0
Order By: Relevance
“…Rheumatoid factor (RF) and anticyclic citrullinated peptide antibody (ACPA) are representative serological markers for RA diagnosis and prognosis, including radiographic progression, but they do not usually correlate with disease progression ( 10 ). Urine soluble CD14 was reported to be a biomarker of high disease activity of RA, but the area under the receiver operating characteristic (ROC) curve was only 0.71 ( 11 ). The disease activity score 28 (DAS28), which is based on the number of tender joint, the number of swollen joint, and the ESR or CRP level, has been widely used for clinical assessment of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid factor (RF) and anticyclic citrullinated peptide antibody (ACPA) are representative serological markers for RA diagnosis and prognosis, including radiographic progression, but they do not usually correlate with disease progression ( 10 ). Urine soluble CD14 was reported to be a biomarker of high disease activity of RA, but the area under the receiver operating characteristic (ROC) curve was only 0.71 ( 11 ). The disease activity score 28 (DAS28), which is based on the number of tender joint, the number of swollen joint, and the ESR or CRP level, has been widely used for clinical assessment of RA.…”
Section: Introductionmentioning
confidence: 99%
“…For many diseases, urine can be used to provide complementary information to that collected via serum measures 7 8 9 . Some urinary chemokines including chemokine (C-C motif) ligand 2 (CCL2) from SLE patients can be potential biomarkers for detecting preclinical renal damage and monitoring renal flares 7 .…”
mentioning
confidence: 99%
“…Urinary collagen fragments also may be useful for early diagnosis of diabetic nephropathy 8 . Previously, we performed quantitative proteome profiling of urine samples from RA patients and non-RA controls using liquid chromatography−tandem mass spectrometry (LC−MS/MS) analysis 9 . Through integrative analysis with transcriptomes of synovial tissues, we demonstrated that proteomic signatures in the urine of RA patients reflect inflammation-related cellular processes, including cell adhesion, immune response, and proteolysis.…”
mentioning
confidence: 99%
“…Previously, Kang et al performed quantitative urinary proteome profiling of urine samples from RA and osteoarthritis (OA) patients using a label-free LC-MS/MS analysis ( 42 ). Using these urinary protein profiles, they identified 134 DEPs between RA and OA urine samples.…”
Section: Exploration Of Novel Biomarkers Using a Proteomic Approachmentioning
confidence: 99%